2018
DOI: 10.1002/chem.201802123
|View full text |Cite
|
Sign up to set email alerts
|

Shape‐Persistent Tetrahedral [4+6] Boronic Ester Cages with Different Degrees of Fluoride Substitution

Abstract: In recent years the interest of shape-persistent organic cage compounds synthesized by dynamic covalent chemistry (DCC) has risen, because these cages are potentially interesting for gas sorption or -separation. One such reaction in DCC is the condensation of boronic acids with diols to form boronic esters. Most interestingly, the variety of geometries and sizes for boronic ester cages is much lower than that of, for example, imine-based cages. Here, a small series of shape-persistent [4+6] tetrahedral boronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 93 publications
1
54
0
Order By: Relevance
“…[195] There are several possible synthetic routes to POCs; imine condensation, [16,22,24,56,144,[146][147][148][196][197][198][199][200][201][202][203][204][205][206] alkyne methasis, [23,194,[207][208][209][210][211][212][213] and boronic ester condensation [122,195,[214][215][216] are the most commonly used (Figure 7a), although there is scope adopt other bond-forming chemistries. [217][218][219] POC synthesis has been discussed in several recent reviews, [6,8,143,183,[219][220][221][222][223] and choice of bond-formation chemistry is important for defining the bond angle between the precursors in the final POC product. This imine condensation react...…”
Section: Designing Porous Organic Cagesmentioning
confidence: 99%
See 2 more Smart Citations
“…[195] There are several possible synthetic routes to POCs; imine condensation, [16,22,24,56,144,[146][147][148][196][197][198][199][200][201][202][203][204][205][206] alkyne methasis, [23,194,[207][208][209][210][211][212][213] and boronic ester condensation [122,195,[214][215][216] are the most commonly used (Figure 7a), although there is scope adopt other bond-forming chemistries. [217][218][219] POC synthesis has been discussed in several recent reviews, [6,8,143,183,[219][220][221][222][223] and choice of bond-formation chemistry is important for defining the bond angle between the precursors in the final POC product. This imine condensation react...…”
Section: Designing Porous Organic Cagesmentioning
confidence: 99%
“…[6,8,183,219,220] For example, Mastalerz et al demonstrated that the geometry and number of dihydroxy groups on triptycene cores could be varied to direct the synthesis of [4+6] or [8+12] cages, when these triptycene precursors were reacted with 1,4-benzenediboronic acid and 1,3,5-benzenetriboronic acid, respectively (Figure 7, where trp = triptycene). [122,221] While organic cages synthesized using boronic acid condensation reactions are somewhat less common than imine cages, [122,195,[214][215][216][239][240][241][242][243][244] the 3758 m 2 g -1 BET surface area reported for the [8+12] boronic acid cage [122] remains after 5 years the highest reported for a POC material. These POCs were designed by mapping their precursors over different platonic solids (Figure 7), where the Reproduced with permission.…”
Section: Designing Porous Organic Cagesmentioning
confidence: 99%
See 1 more Smart Citation
“…The broadness of the signals is expected because typically the alkene metathesis is not of high E / Z ‐selectivity [9] and each of the 24 formed internal olefinic bonds is probably present in two isomeric forms resulting a vast set of overall 2 24 (16,777,216) possible stereoisomers! [20] Unfortunately, for cage 10 , no clear reliable mass spectrometric information to underpin the successful metathesis was achieved. However, it is worth mentioning that for some boronic ester cages these were also not detectable by MS, although clearly have been identified by single crystal X‐ray diffraction [4f, 21] …”
Section: Figurementioning
confidence: 99%
“…Mastalerz and coworkers synthesized three shape-persistent tetrahedral boronic ester cages 15a-c ( Figure 10) by the [4+6] condensation between nonfluorinated or fluorinated diboronic acids 13a-c and a brominated triptycene-based hexaol 14. 74 The fluorinated diboronic acids 13b and 13c have higher Lewis acidity than the nonfluorinated 13a, which reduced the reaction time Cooper and coworkers performed a side-by-side comparison of the fluorinated and nonfluorinated imine-based cages. 75 Using a [4+6] cycloimination of 1,3,5-triformylbenzene (16, Figure 11) with (R,R)-1,2-diphenylethylenediamine (17a) and (R,R)-1,2-bis(4-fluorophenyl)ethane-1,2-diamine (17b), they synthesized two novel imine cages 18a (R ¼ H) and 18b (R ¼ F).…”
Section: Porous Fluorinated Cagesmentioning
confidence: 99%